Analysis Of Factors Affecting The Performance Of Nurses In Raden Mattaher Regional General Hospital Jambi Province - Firza Khairullah Sembiring; Kamelia Kaban; Maya Sari Mutia; Ermi Girsang (CV. Inara, 2022)
The performance of nurses in hospitals is closely related to reliable, skilled, and professional human resources. Many factors are thought to influence the performance of nurses, namely age, education, length of work, training, motivation, incentives, work environment, and supervision. The purpose of this study was to analyze the factors that influence the performance of nurses. This research is an analytical study with a cross-sectional approach. The research was conducted at Raden Mattaher Hospital, Jambi Province. The study population was 406 people and a sample of 261 people. Sampling by purposive sampling. Data analysis was univariate, bivariate with a chi-square test, and multivariate with multiple logistic regression at a 95% confidence level (=0.05). The results showed that the factors that influenced the performance of nurses at the Raden Mattaher Regional General Hospital Jambi Province were education and training (p=0.000), motivation (p=0.000), incentives (p=0.020), and supervision (p=0.002 ). Variables that had no effect were age (p=0.584), education (p=0.786), length of work (p=0.421), and work environment (p=0.166). The most dominant variable affecting the performance of nurses is motivation with a value of Exp(B)/OR = 5.626, meaning that nurses who have high motivation have a 5.6 times higher chance of good performance than nurses with low motivation. This study concludes that education and training, motivation, incentives, and supervision affect the performance of nurses. The leadership of the Raden Mattaher Hospital in Jambi Province needs to hold regular education and training, provide incentives according to the nurse's responsibilities, the head of the room supervises properly so that it can improve the performance of implementing nurses.